Miniature tool for characterization of supercapacitive charge storage - Kunwar, Ria; Izan Izwan, Misnon; Hamdan, Daniyal; Rajan, Jose (2021)
A new protocol to characterize supercapacitive charge storage parameters from discharge voltage measurement and using an electrical model is presented. A distribution of capacitances and resistances in three charge storing time domains (fast, medium, and slow) are derived through this protocol. The method relieson recording the self-discharge data (open circuit discharge) and using it along with the charge redistribution within the supercapacitor to obtain the parameters for the equivalent circuit model. The results are validated using the galvanostatic charge discharge cycling. The method proposed here uses comparatively lesser number of variables, thereby making it easier to compute and the validation shows a good match between the experimental and the simulated results.